Characterization of Platymessa with redescription of the type species and a new generic synonymy (Arachnida, Opiliones, Cosmetidae) - Medrano, Miguel; Kury, Adriano B. (Zootaxa, 2016)
The genus Platymessa was originally described by Mello-Leitão and diagnosed following the Roewerian system. It originally included two species from the Colombian Andes. Subsequently, a third species was described: Platymessa transversalis Roewer, 1963, which is herein transferred to the genus Chusgonobius Roewer, 1952, forming the new combination Chusgonobius transversalis. Herein, an emended diagnosis is given to Platymessa, the type species, Platymessa h-inscriptum Mello-Leitão, 1941, is redescribed and P. nigrolimbata Mello-Leitão, 1941 is considered its junior subjective synonym. Brachylibitia Mello-Leitão, 1941, is herein considered a junior subjective synonym of Platymessa and its type species, Brachylibitia ectroxantha Mello-Leitão, 1941, considered a species inquirenda, forming the new combination Platymessa ectroxantha. Genital morphology of Platymessa h-inscriptum is described and some characters are discussed regarding their importance in cosmetid taxonomy. Novel forms of sexual dimorphism are described in coxa IV.